English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

5 answers

g(a+1) - g(a)
= 3(a+1)+5 - (3a + 5)
= 3a + 3 + 5 - 3a - 5
= 3

2006-09-25 13:55:55 · answer #1 · answered by Isaac 2 · 1 1

g(a + 1) = 3(a + 1) + 5 = 3a + 3 + 5 = 3a + 8


g(a + 1) - g(a) = (3a + 8) - (3a + 5)
g(a + 1) - g(a) = 3a + 8 - 3a - 5
g(a + 1) - g(a) = 3

2006-09-25 17:01:04 · answer #2 · answered by Sherman81 6 · 0 0

g(a+1)-g(a)= 3(a+1)+5 - 3a-5
= 3a+3+5-3a-5
=3

(do not listen to yahoo adict!
he has no idea what he is writing.)

2006-09-25 14:02:06 · answer #3 · answered by Anonymous · 0 0

g(a+1) = 3(a+1)+5 = 3a + 8
g(a) = 3(a)+5 = 3a + 5
g(a+1)-g(a) = 3a + 8 - (3a + 5) = 3

2006-09-25 13:54:47 · answer #4 · answered by Ben 2 · 1 1

the previous answer is wrong

g(a+1) - g(a)
ga + 1g - ga
=g
= 3t+5
are u in elementary school
too young for this site****

2006-09-25 13:56:20 · answer #5 · answered by Man 5 · 0 2

fedest.com, questions and answers